Comparison of valve-sparing techniques for surgical treatment of aortic root pathology: Florida Sleeve vs David procedure - V. U. Efendiev; V. K. Noginov (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Such reconstructive operations on the aortic root as the David and Florida Sleeve procedures are fundamentally different in prosthetics of the aortic root with reimplantation of the ostiums of the coronary arteries into the prosthesis during David surgery and preservation of all native structures of the aortic root without reimplantation of the ostiums of the coronary arteries during Florida Sleeve surgery. Both procedures effectively reduce the dilated aortic ring, however, the Florida Sleeve procedure is performed much less frequently than the David procedure.The OBJECTIVE was to study and analyze literature sources that present a comparison of the results of valve-preserving Florida Sleeve and David procedures.METHODS AND MATERIALS. A search was conducted in PubMed and e-library databases from 2005 to 12.06.2023 for search queries. The studies were selected according to the PRISMA algorithm.RESULTS. According to the results of search queries, 18 articles were found, 2 articles satisfying the selection criteria were included in the analysis. The meta-analysis was not carried out due to the pronounced heterogeneity of the data. In both studies, a statistically significant shorter time of cardiopulmonary bypass and aortic occlusion takes when performing Florida Sleeve compared to David procedure. Short-term and long-term 5-year results of operations did not show statistically significant difference.